Hypogonadism. Diagnosis, masculinity, and capital in narratives about testosterone deficiency. Issue 1 (2nd January 2023) - Berg, Linda; Linander, Ida
ABSTRACT: For centuries, male hypogonadism has been defined as a clinical syndrome caused by the inability to produce physiological concentrations of testosterone and/or normal amount of sperm. In 2020, an information campaign started in Sweden with the ambition of increasing knowledge about hypogonadism and (lack of) testosterone, targeting both men and healthcare providers. In this study, we take a closer look at media discussions in Sweden on hypogonadism over the period 2018–2021. Through feminist thinking on biomedicalisation, we analyse the media material about the phenomena and issues being raised regarding masculinity, age and health in contemporary neoliberal and biocapital times. For some people, hypogonadism is a severe condition, but we can also see that the diagnosis becomes a response to a wide range of symptoms, expanding the realm for diagnostic practices and tying into normative ideas about age, time and lacking or fading masculinity. The media narratives about hypogonadism not only reflect cultural norms regarding masculinity and the plasticity of diagnoses but also create desires, needs and markets.